Re-Conceptualizing Success: Investigating Specialized Units Responses to the Sexual Trafficking of Female Victim-Survivors. (December 2022) - Ballucci, Dale; Stathakis, Felicia
This paper explores police officers' experiences working in a specialized human trafficking unit in Canada to identify challenges, strategies, and responses to working with victim-survivors. Analyzing data from semi-structured interviews, we find that officers deploy victim-centered responses reflecting procedural justice outcomes due to their awareness that the criminal justice process often re-victimizes. Officers' deployment of procedural justice acknowledges the victim-survivor trauma, but also allows them to build a stronger case through evidence gathering, increasing the potential for charges and convictions, also known as distributive justice. We argue that this illustrates that these two approaches to justice are interdependent.